On the heaviness of feathers, or what has culture got to do with the failure to establish an organic poultry production business in contemporary Serbia? - Slobodan Naumović (University of Belgrade, 2016)
This case study starts from the thesis that the analysis of life histories, coupled by observation of actual behaviour, can contribute to a more nuanced understanding of the ways in which overarching categories like "socio-economic cultures" actually function in the local and national settings. It is based on in-depth interviews with a former top manager in the agro-veterinary section of a Serbian export-import firm. The informant presents the reasons that have influenced him to leave his job and attempt to establish an organic agro-business, offers a personal view of political and cultural factors that have caused the decline of Yugoslav and Serbian economies, and explains how these factors have influenced his business and family survival strategies, among which exploitation of family work and instrumentalisation of kinship and neighbourhood networks were most prominent. The case study thus reveals the actual "cultural resources" that the informant was ready to turn to in order to sustain his entrepreneurial efforts. Next, the case study suggests that "narrow" professional cultures, like managerial or entrepreneurial cultures, can have more impact on individual behaviour than "broader" national or regional cultures. In that sense, when the functioning of national "socio-economic culture(s)" is properly contextualized, then it has to be seen as neither the only, nor the principal factor that can explain observable behaviour, particularly in rapidly changing political, economic, institutional, and legal settings, characterised by lingering state capitalism, conquering predatory capital accumulation, semi-functional legal system, agricultural policy breakdown, and rampant corruption.